In vivo cardiac pacemaker function of differentiated human mesenchymal stem cells from adipose tissue transplanted into porcine hearts - Darche, Fabrice Fernand; Rivinius, Rasmus; Rahm, Ann-Kathrin; Köllensperger, Eva; Leimer, Uwe; Germann, Günter; Reiss, Miriam; Koenen, Michael; Katus, Hugo; Thomas, Dierk; Schweizer, Patrick Alexander (World journal of stem cells, 2020)
Background: Mesenchymal stem cells (MSC) modified by gene transfer to express cardiac pacemaker channels such as HCN2 or HCN4 were shown to elicit pacemaker function after intracardiac transplantation in experimental animal models. Human MSC derived from adipose tissue (haMSC) differentiate into cells with pacemaker properties in vitro, but little is known about their behavior after intracardiac transplantation. Aim: To investigate whether haMSC elicit biological pacemaker function in vivo after transplantation into pig hearts. Methods: haMSC under native conditions (nhaMSC) or after pre-conditioning by medium differentiation (dhaMSC) (n = 6 pigs each, 5 × 106 cells/animal) were injected into the porcine left ventricular free wall. Animals receiving PBS injection served as controls (n = 6). Four weeks later, total atrioventricular (AV)-block was induced by radiofrequency catheter ablation, and electronic pacemaker devices were implanted for backup stimulation and heart rate monitoring. Ventricular rate and rhythm of pigs were evaluated during a follow-up of 15 d post ablation by 12-lead-ECG with heart rate assessment, 24-h continuous rate monitoring recorded by electronic pacemaker, assessment of escape recovery time, and pharmacological challenge to address catecholaminergic rate response. Finally, hearts were analyzed by histological and immunohistochemical investigations. Results: In vivo transplantation of dhaMSC into the left ventricular free wall of pigs elicited spontaneous and regular rhythms that were pace-mapped to ventricular injection sites (mean heart rate 72.2 ± 3.6 bpm; n = 6) after experimental total AV block. Ventricular rhythms were stably detected over a 15-d period and were sensitive to catecholaminergic stimulation (mean maximum heart rate 131.0 ± 6.2 bpm; n = 6; P < 0.001). Pigs, which received nhaMSC or PBS presented significantly lower ventricular rates (mean heart rates 47.2 ± 2.5 bpm and 37.4 ± 3.2 bpm, respectively; n = 6 each; P < 0.001) and exhibited little sensitivity towards catecholaminergic stimulation (mean maximum heart rates 76.4 ± 3.1 bpm and 60.5 ± 3.1 bpm, respectively; n = 6 each; P < 0.05). Histological and immunohistochemical evaluation of hearts treated with dhaMSC revealed local clusters of transplanted cells at the injection sites that lacked macrophage or lymphocyte infiltrations or tumor formation. Intense fluorescence signals at these sites indicated membrane expression of HCN4 and other pacemaker-specific proteins involved in cardiac automaticity and impulse propagation. Conclusion: dhaMSC transplanted into pig left ventricles sustainably induced rate-responsive ventricular pacemaker activity after in vivo engraftment for four weeks. The data suggest that pre-conditioned MSC may further differentiate along a pacemaker-related lineage after myocardial integration and may establish superior pacemaker properties in vivo.